Flaubert's parrot ; A history of the world in 10 1/2 chapters - Barnes, Julian (Everyman's library, 2012)
Flaubert's parrot: Relates a cranky amateur scholar's search for the truth about Gustave Flaubert, and the obsession of this detective whose life seems to oddly mirror those of Flaubert's characters. History of the world in 10 1/2 chapters: An eccentiric, playfully skewed, surprisingly comprehensive chronicle of life on planet Earth. A novel whose threads of coincidence and hidden connection are woven into a narrative tapestry brilliant with wit, intelligence, and emotion.